Bullying Experience Among Trainees of Moral Rehabilitation School - Wazir, Mohd Nor Hafiz Bin Mohd; Chethiyar , Saralah Devi Mariamdaran (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
Bullying is one of the criminal misconduct or deviant behaviour that occurs in society  today. This bullying activity is also common among teenagers either at the school or  tertiary level. This problem also occurs among juvenile trainees who are undergoing  rehabilitation in correctional institutions. This quantitative study was conducted  to explore the issues and problems of bullying based on the actual experience of the  respondents. A total of 109 trainees of the Moral Rehabilitation School were selected using  purposive sampling. The research data were collected by employing the questionnaires  with a structured self-completed instrument known as the Revised Malaysian Bullying  Questionnaire (RMBQ). The findings of this study indicate that the participants in this  study report receiving and perpetrating relatively low amounts of bullying. Further, the  findings of the study revealed that the level of bullying among the trainees of Moral  Rehabilitation School differ in terms of gender. The suggestion from the findings of this  study is that the Moral Rehabilitation School should raise awareness among trainees by  conducting bullying awareness programs and awareness campaigns.
Keywords: Bullying; Juvenile; Deviant; Moral Rehabilitation School